2021
DOI: 10.1155/2021/9946183
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm Activity of Extract and a Compound Isolated from Triumfetta welwitschii against Pseudomonas aeruginosa

Abstract: Triumfetta welwitschii has been used as a traditional medicine in Africa. It is documented as a rich source of phytochemicals with antibacterial activities. To further explore the antibacterial potential of these phytochemical components, the phytochemical profile of the dichloromethane: methanol leaf extract from T. welwitschii was investigated using ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). Compounds were isolated from the extract using column chromatography and thin-laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…A similar trend was observed for the inhibition of mature biofilm, where the biofilms had accumulated biomass. These findings are in tandem with results obtained in a study carried out by Mombeshora et al [ 5 ], where the compound tested did not have any disruptive effect on mature (72 h) biofilms of P. aeruginosa , a Gram-negative bacterium like K. pneumoniae . This can also be attributed to the opinion of Kelmanson et al [ 49 ], who noted that more resistance to external agents is often shown once biofilms have been fully established; therefore, the disruption of mature biofilms tends to require higher doses of disrupting agents than those needed to destroy planktonic cells.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A similar trend was observed for the inhibition of mature biofilm, where the biofilms had accumulated biomass. These findings are in tandem with results obtained in a study carried out by Mombeshora et al [ 5 ], where the compound tested did not have any disruptive effect on mature (72 h) biofilms of P. aeruginosa , a Gram-negative bacterium like K. pneumoniae . This can also be attributed to the opinion of Kelmanson et al [ 49 ], who noted that more resistance to external agents is often shown once biofilms have been fully established; therefore, the disruption of mature biofilms tends to require higher doses of disrupting agents than those needed to destroy planktonic cells.…”
Section: Discussionsupporting
confidence: 89%
“…Klebsiella pneumoniae , a Gram-negative bacterium belonging to the family Enterobacteriaceae , has been reported to form biofilms that often adhere to surfaces such as lungs, livers, and central venous catheters which are implicated in prominent nosocomial and community-acquired infections [ 5 ]. These infections include pneumonia, urinary tract infections (UTIs), bloodstream infections, necrotizing fasciitis, pyogenic liver abscess, endophthalmitis, and meningitis, among others, subsequently affecting the morbidity and mortality rate, particularly in critically ill and immunocompromised patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrate content was evaluated by performing phenol sulfuric acid (PSA) assay and measuring the absorbance of furfural compound at ∼490 nm wavelength by taking glucose as a standard. 23 Similarly, protein content was evaluated by performing bicinchoninic acid (BCA) assay, measuring the absorbance at ∼562 nm. In the same manner, the eDNA content was also evaluated by purifying the eDNA with proteinase K, and RNase.…”
Section: Methodsmentioning
confidence: 99%
“…Environmental Science: Nano Paper by taking glucose as a standard. 23 Similarly, protein content was evaluated by performing bicinchoninic acid (BCA) assay, measuring the absorbance at ∼562 nm. In the same manner, the eDNA content was also evaluated by purifying the eDNA with proteinase K, and RNase.…”
Section: Evaluating the Composition Of Ecm-f Ec And Ecm-f Samentioning
confidence: 99%
“…The Petri dishes were incubated for 24 hours at 37˚C. The CMB was visibly deduced as being the first dish devoid of bacteria [17].…”
Section: Determination Of Minimum Inhibitory Concentration (Mic) and ...mentioning
confidence: 99%